Collateral Valuation and Borrower Financial Constraints: Evidence from the Residential Real Estate Market - Agarwal, Sumit; Ben-David, Itzhak; Yao, Vincent (Management Science, 2015)
Financially constrained borrowers have the incentive to influence the appraisal process in order to increase borrowing or reduce the interest rate. We document that the average valuation bias for residential refinance transactions is above 5%. The bias is larger for highly leveraged transactions, around critical leverage thresholds, and for transactions mediated through a broker. Mortgages with inflated valuations default more often. Lenders account for 60%–90% of the bias through pricing. This paper was accepted by Wei Jiang, finance.